Comparison of the effect of group transdiagnostic therapy and group cognitive therapy on anxiety and depressive symptoms. - Abolfazl Mohammadi; Behrooz Birashk; Banafsheh Gharaie (Tehran University of Medical Sciences, 2013)
The cognitive behavioral interventions based on the transdiagnostic approach for emotional disorders have received useful empirical supports in recent years. Most of the researches on this area have been conducted without any control group. Moreover, little information about comparative effectiveness has reported. The current study was compared transdiagnostic group therapy with classical cognitive group therapy.Thirty three collages students with anxiety and depressive symptoms participated in eight two-hour sessions in Akhavan Hospital, Tehran, Iran during May and June 2011. The results were analyzed by The Depression, Anxiety, and Stress Scale, and Work and Social Adjustment Scale in pre and post intervention.Both groups showed the significant difference in research variables pre and post test. However, there was no significant difference in the results analysis using ACOVAs except for anxiety symptoms.The effectiveness of transdiagnostic group therapy was confirmed in reducing anxiety and depressive symptoms. Implications of the study are discussed.